2011
DOI: 10.1007/s00018-011-0694-6
|View full text |Cite
|
Sign up to set email alerts
|

LAPTM4A interacts with hOCT2 and regulates its endocytotic recruitment

Abstract: Human organic cation transporter 2 (hOCT2) is involved in the transport of endogenous and exogenous organic cations mainly in cells of the kidney and the brain. Here, we focus on the regulation of hOCT2 by direct protein-protein interaction. Screening within a mating-based split-ubiquitin-yeast-two-hybrid system (mBSUS) revealed the lysosomal-associated protein transmembrane 4 alpha (LAPTM4A) as a potential interacting protein. Interaction of LAPTM4A and hOCT2 was confirmed by pulldown assays, FRET microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…A subset of fluorescence emanated from nucleoli, potentially resulting from nonspecific primary antibody binding, although Stx has been reported to be actively transported into nucleoli ( 51 ). Unexpectedly, as prior studies localized LAPTM4A to lysosomes ( 31 34 ), we found that a LAPTM4A-GFP fusion protein localized to the Golgi complex, like TM9SF2 ( Fig. 5A ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…A subset of fluorescence emanated from nucleoli, potentially resulting from nonspecific primary antibody binding, although Stx has been reported to be actively transported into nucleoli ( 51 ). Unexpectedly, as prior studies localized LAPTM4A to lysosomes ( 31 34 ), we found that a LAPTM4A-GFP fusion protein localized to the Golgi complex, like TM9SF2 ( Fig. 5A ).…”
Section: Resultssupporting
confidence: 81%
“…The LAPTM4A locus has been reported to encode a transmembrane protein localized to lysosomes and late endosomes. It has been linked to intracellular transport of nucleosides, multidrug resistance, and maintenance of lysosomal integrity ( 31 34 ). In addition to the enrichment of guides targeting TM9SF2, LAPTM4A, and genes related to sphingolipid biosynthesis, our analysis detected enrichment for guides targeting several genes associated with cancer and cell proliferation (MLLT3, TFAP4, ZNF217, and DUSP6) ( 35 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…B1–B2‐linked full‐length cDNA for hOCT1, −2, or −3 was cloned in vivo in frame into the expression vector pMetYCgate containing the Cub and the transcription factor protA‐LexA‐VP16 peptide and expressed in the reporter yeast strain THY.AP4. Expression was verified by Western blot analyses (29, 30). Yeast cells expressing hOCTs were cotrans‐formed with a human cDNA kidney library expressed in the vector pPR3‐N (Dualsystems Biotech, Schlieren, Switzerland) along with the Nub.…”
Section: Methodsmentioning
confidence: 99%
“…However, it should be considered that the function of these transporters is strongly determined by the interaction with other cellular proteins, which modulate their activity and determine their cellular fate. For example, a direct interaction of hOCT2 with the lysosomal‐associated protein transmembrane 4α (LAPTM4A) has been demonstrated . This interaction influences transporter trafficking to and from the cell membrane and processing via the intracellular sorting machinery.…”
Section: Targeted Chemotherapeutic Drugsmentioning
confidence: 99%
“…For example, a direct interaction of hOCT2 with the lysosomal-associated protein transmembrane 4α (LAPTM4A) has been demonstrated. 138 This interaction influences transporter trafficking to and from the cell membrane and processing via the intracellular sorting machinery. Of course SNPs of proteins that are part of the proteome of the transporters have potentially important implications for transporter function and should be taken into account in future studies.…”
Section: Metforminmentioning
confidence: 99%